Intensitas Bermain Game Online Terhadap Perilaku Prososial Siswa - Anna Rufaidah; Dian Renata; Sri Utami; Afiatin Nisa; Hengki Satrianta; Sabrina Dachmiati (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
Prosocial behavior was expected to grow and develop in students. In fact there were still students who have not been able to develop prosocial behavior due to many factors, one of which is the effect of the intensity of playing online games. This study aims to determine the contribution of the intensity of playing online games to students' prosocial behavior. This research uses a quantitative approach with the type of ex-post facto. The population in this study were all students of SMP Negeri 137 Jakarta with a total of 230 students. Samples were drawn randomly which were estimated using the Slovin formula with an error degree of 5% so that the number of samples was known to be 147 students. Data was collected through the technique of playing online game intensity scales and prosocial behavior. Data were analyzed descriptively and inferentially. The research results show that: a. the intensity of playing online games is in the medium category, b. prosocial behavior in the low category, and c. the intensity of playing online games has a significant effect on students' prosocial behavior.